Final review draft: WIRED resource adequacy working group report - Unidentified author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2020)
The goal of the Resource Adequacy work group was to develop a common understanding of RA and reliability and to explore the potential benefits of regional approaches to RA. The work group gave special consideration to the fact that there is variation in the approaches used for RA in the West today, both at the regional level and among utilities. Given the importance of RA, the work group's main objective was to provide a set of principles and recommendations for Western governors to consider as they explore greater regional collaboration as an opportunity to achieve state policy objectives.
WIRED resource adequacy working group report
In early 2020, the Center for the New Energy Economy (CNEE), at the request of the Western Energy Industry Leaders (WEIL), convened a group of Western governors' energy advisors along with a small but diverse group of experts representing utilities, power marketing administrations, renewable energy companies and clean energy advocates, collectively referred to as the "Western Interconnection Regional Electricity Dialogue" (WIRED). The goal of this effort is to provide a set of recommendations to governors by the end of the year. To achieve this goal, CNEE has facilitated a series of work group meetings to discuss and analyze a range of regional electricity issues including resource adequacy (RA), state clean energy and climate policies, and transmission development.
Keywords: Western Interconnect Regional Electricity Dialogue (WIRED); Clean energy; Clean energy -- Accounting; Clean energy -- Compliance; Electric power production; Electric power distribution; resource adequacy (RA)